2000
DOI: 10.3171/jns.2000.92.6.0955
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization of cerebral arteriovenous malformations with silk sutures: analysis and clinical correlation of complications revealed on computerized tomography scanning

Abstract: Silk sutures are an effective and relatively safe embolic agent. After brain AVM embolization with silk sutures, new abnormalities were found on CT scans obtained in one of eight procedures. When a new CT finding occurred, the patient had roughly equal chances of having no new symptoms, having new transient neurological deficits, or having new permanent neurological deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…9,30 The incidence of endovascular embolization-induced delayed hemorrhage is not frequent and ranges from 3 to 5%. 4,12,17,21 In our series, however, we found only one case of delayed hemorrhage, in which there were no clinical signs. In our series, there was no angiographic evidence of vasculitis, and histological analysis showed no or only a nonspecific inflammatory response.…”
Section: Discussionmentioning
confidence: 39%
See 4 more Smart Citations
“…9,30 The incidence of endovascular embolization-induced delayed hemorrhage is not frequent and ranges from 3 to 5%. 4,12,17,21 In our series, however, we found only one case of delayed hemorrhage, in which there were no clinical signs. In our series, there was no angiographic evidence of vasculitis, and histological analysis showed no or only a nonspecific inflammatory response.…”
Section: Discussionmentioning
confidence: 39%
“…25 As expected, the most common complication is cerebral infarction in the territory of the embolized vessels. Song, et al, 21 reported 26 cases of presumed acute ischemia in a series in which 230 embolization procedures were performed. In addition to occlusion of the vessel by the embolic agent, ischemia may result from an autologous clot produced by manipulation of the catheter or guidewire.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations